Physical quality test of jamblang fruit ethanol extract antioxidant cream (Syzygium cumini (l.) Skeels) - Yuniharce Kadang; Megawati (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2024)
Background: Antioxidants are compounds that can protect against oxidative stress caused by free radicals, both from inside the body (endogenous) and outside (exogenous). Many plants have antioxidant properties, including gambling (Syzygium cumini (L.) Skeels). This plant is known to have various bioactive components that can capture and neutralize free radicals; Jamblang fruit has antioxidant activity caused by the content of flavonoid compounds in it. These compounds can be utilized as topical preparations for skin care products. Objective: This study aims to determine the effect of ethanol extract concentration of jamblang fruit (Syzygium cumini (L.) Skeels) on the physical stability of the cream. Methods: This research is conducted in an experimental laboratory. Jamblang fruit extract was obtained using the maceration method using 96% ethanol. The extract was then formulated in the form of a m/a type cream preparation with concentration variations of 1% (FI), 2% (F2), and 3% (F3). The physical stability test of the cream includes viscosity, spread, adhesion, and pH value tests. The data is analyzed to determine the effect of adding extracts and the storage time on the physical stability of the cream. Results: The test showed that an increase in the concentration of ethanol extract from jamblang fruit led to a decrease in pH value, viscosity value, and adhesion and could increase dispersion. It was concluded that the variation in the concentration of ethanol extract from jamblang fruit influenced the physical properties of M/A cream. Conclusion: It can be concluded that the variation in the concentration of ethanol extract of jamblang fruit affects the physical properties of the oil cream in water (M/A). The effects caused include a decrease in pH value, a reduction in viscosity, a decrease in adhesion, and an increase in dispersion. These changes will ultimately affect the physical stability of the cream preparation.